(Lysine avalabity as indicator for protein quality) - Nuraini, Dhiah (Balai Besar Industri Agro, 1991)
Protein is one of the nutrients needed for man living and growing normally.Nutritive value of protein is determined by its ammount and also by the composition of its amino acid.Lysine is one of the essential amino acids found in various food stuffs.Lysine is sometimes used as an indicator for determination of protein quality.It is due to the fact that lysine sometimes found as a limiting essential amino acid, especially in cereal.It is also caused lysine is themost sensitive amino acid to certain processing treatment such as heating,smoking,frying and also involved in mailliard reaction.Other important reason is that lysine can be determined by chemical analysis, not like other amino acids which have to be determined biologically.